HARMONI DALAM KEBERAGAMAN: ANALISIS KORELASI SIKAP TOLERANSI BERAGAMA DAN INTERAKSI SOSIAL PESERTA DIDIK - Nandia Ayuzmal; Heru Juabdin Sada; Zahra Rahmatika (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2026)
Religious tolerance is one of the essential character values in fostering harmonious social relationships within a multicultural educational environment. A low level of religious tolerance may negatively affect the quality of students' social interactions, as reflected in the formation of exclusive peer groups, limited openness to differing opinions, and a lack of appreciation for diversity. This study aims to examine the relationship between religious tolerance and students’ social interactions. This research employed a quantitative approach using an ex-post facto correlational design. The population consisted of all eighth-grade students at SMP Negeri 22 Bandar Lampung, totaling 395 students. Data were collected through a structured questionnaire that had been tested for validity and reliability using Pearson’s correlation and Cronbach’s Alpha. Data analysis included normality testing, linearity testing, and Pearson Product-Moment correlation analysis. The findings revealed a correlation coefficient of with a significance level of (below the significance level of ). These results indicate a positive and statistically significant relationship, categorized as strong, between religious tolerance and students’ social interactions. Therefore, the higher the level of religious tolerance possessed by students, the better the quality of their social interactions. Religious tolerance, reflected in the ability to accept differences, respect others’ beliefs, demonstrate patience, uphold religious freedom, and maintain social harmony, contributes significantly to improving the quality of students’ social interactions within the school environment.